Communication Strategy in Assisting Surabaya Hero Cadres (KSH) in Gunung Sari Village, Dukuh Pakis Subdistrict, Surabaya City - Pranata, Ikhsan Hendra Hadi; Ansori, Moh. (Proceedings of International Conference on Da'wa and Communication, 2024)
This study discusses the communication strategy in assisting the Surabaya Hero Cadres through plastic waste management in RW 01, Gunung Sari Village, Dukuh Pakis Subdistrict, Surabaya City. The research focuses on two crucial aspects: the communication strategy in the empowerment assistance provided to the Surabaya Hero Community and the social changes resulting from the post-assistance empowerment. The research approach used is ABCD (Asset-Based Community Development), based on the principles, stages, and procedures of 5D: Discovery, Dream, Design, Define, and Destiny. The results show that the communication strategy developed by the researchers is an active participatory communication model. This communication strategy successfully motivated and developed the creativity of the Surabaya Hero Cadres (KSH) in RW 01, Gunung Sari Village, Dukuh Pakis Subdistrict, Surabaya City in managing their assets. The social changes resulting from the empowerment assistance show that KSH has managed to create a clean environment and transform plastic waste into various handicrafts with economic value, thereby increasing economic income.